EFFECTIVE CLEANING AND DECONTAMINATION OF THE INTERNAL AIR AND WATER CHANNELS, HEADS AND HEAD-GEARS OF MULTIPLE CONTRA ANGLE DENTAL HANDPIECES USING AN ENZYMATIC DETERGENT AND AUTOMATED WASHER DISINFECTION IN A DENTAL HOSPITAL SETTING - Coleman, David; Deasy, Emily; O'Donnell, Mary (My University, 2022)
Background Dental handpieces (DHPs) are reusable invasive medical devices that must be cleaned, decontaminated, lubricated and steam sterilized after use. DHPs have a complex internal design including narrow channels, contamination of which can compromise sterilization. DHPs are not designed for routine disassembly, making cleaning/decontamination efficacy difficult to monitor. Washer-disinfection is the preferred method of decontaminating DHPs, but few studies have investigated its direct effectiveness at reducing microbial contamination internally. Aims To use contra angle DHPs as a model system to investigate the effectiveness of washer-disinfection at reducing microbial contamination of internal components of multiple DHPs. Methods The air and water channels and heads of 10 disassembled contra angle DHPs (BienAir, Switzerland) were inoculated separately with 108 colony forming units (CFU) of Pseudomanas aeruginosa, Staphylococcus aureus, Enterococcus hirae or Candida albicans in the presence of 0.3% bovine serum albumin (BSA) (clean conditions), 3.0% BSA or 10% artificial test soil (dirty conditions). After reassembly, all 10 DHPs underwent washer-disinfection simultaneously in a Míele (Míele Ltd., Ireland) PG8528 washer-disinfector and were tested for reductions in microorganisms and protein. Additional experiments were undertaken with three lubricated DHPs inoculated with S. aureus and 10% test soil. All experiments were repeated in triplicate. Findings On average an approximate 5 log or greater reduction in microbial CFUs and a >93% reduction in protein from DHP heads and channels was consistently recorded following washer-disinfection for all DHPs under all conditions tested. Conclusions The internal components of multiple DHPs can be effectively cleaned and decontaminated by washer-disinfection.
PUBLISHED
6th August 2022, Epub ahead of print
Keywords: Contra angle dental handpiece; washer disinfector; decontamination; water and air channels; dental handpiece heads and gears; process challenge microorganisms; Staphylococcus aureus; Enterococcus hirae; Pseudomonas aeruginosa; Candida albicans; handpiece lubrication; Immunology, Inflammation & Infection; Automated washer disinfection; DENTAL HANDPIECES; Decontamination of medical device internal lumens; Decontamination of reusable invasive medical devices